The Factor Analysis of Contactless Services and Its Impact Towards Employee Performance of BPJS Ketenagakerjaan Gresik Branch Office during the Covid 19 Pandemic with Work Family Conflict Mediation - Rasyid, Ravika Imania; Hidayati, Ernani; Muawanah, Umi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The contactless service implemented by BPJS Ketenagakerjaan during the Covid-19 pandemic changed the way of work, from working at office to working remotely or work from home. Work from home also possible to cause work family conflict. Based on research of BPJS Ketenagakerjaan Gresik the researcher focuses on the influence of contactless service factors on the performance of BPJS Ketenagakerjaan Gresik employees. This research aims to determine the influence of contactless service factors on the performance of BPJS Ketenagakerjaan Gresik employees during the Covid-19 Pandemic with work family conflict as mediation. The method in this research was used quantitative methodology, by examining the relationship between contactless services (as measured by the cognitive demand dimension, off-work hours technology assisted job demands (off-TAJD), the perception of stress related to ICT use to stay connected with others, and recovery experience), work-family conflict, and employee performance.